Race, identity, and citizenship - Torres, Rodolfo D.; Mirón, Louis F.; Inda, Jonathan Xavier (Blackwell, 1999)
Mapping the languages of racism. Critical multiracial feminisms. Fashioning mixed race. The color(s) of whiteness. Cultural citizenship, multiculturalism, and the state. Locating class. Globalized futures and racialized identities. Critical engagements.